2016
DOI: 10.1161/circulationaha.115.017888
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Clinical Outcome in Mitral Regurgitation With Cardiovascular Magnetic Resonance Quantification

Abstract: Background— Surgery for severe mitral regurgitation is indicated if symptoms or left ventricular dilation or dysfunction occur. However, prognosis is already reduced by this stage, and earlier surgery on asymptomatic patients has been advocated if valve repair is likely, but identifying suitable patients for early surgery is difficult. Quantifying the regurgitation may help, but evidence for its link with outcome is limited. Cardiovascular magnetic resonance (CMR) can accurately quantify mitral reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
100
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 43 publications
(51 reference statements)
7
100
1
2
Order By: Relevance
“…There was a trend toward superior performance of TTE-derived by CMR-derived regurgitant volume and fraction and need for mitral valve surgery; however, they also reported that TTE measurements did not predict the need for valve surgery. 22 Our results are discordant in that we found a trend toward better prediction of outcomes with TTE as compared to CMR. The reason for this discordance is unclear but notable differences in study design were that echocardiography used in the current study was done as a part of the research protocol as opposed to This study has several limitations.…”
Section: Accepted Manuscriptcontrasting
confidence: 70%
“…There was a trend toward superior performance of TTE-derived by CMR-derived regurgitant volume and fraction and need for mitral valve surgery; however, they also reported that TTE measurements did not predict the need for valve surgery. 22 Our results are discordant in that we found a trend toward better prediction of outcomes with TTE as compared to CMR. The reason for this discordance is unclear but notable differences in study design were that echocardiography used in the current study was done as a part of the research protocol as opposed to This study has several limitations.…”
Section: Accepted Manuscriptcontrasting
confidence: 70%
“…Gelfand et al previously found that CMR-RF thresholds for MR with maximal agreement with echo were mild ≤ 15%, moderate 16–24%, moderate-severe 25–42%, severe > 42% [47]. More recently, Myerson et al showed that a Rvol threshold of > 55 mL and RF > 40% accurately identified patients who progressed to symptomatic MR or other indications for mitral valve surgery [51]. These studies suggest that CMR-specific thresholds need to be better defined.…”
Section: Mitral Valvementioning
confidence: 99%
“…Cardiovascular magnetic resonance (CMR) is able to quantify MR with high accuracy and reproducibility using a combination of left ventricle (LV) volumetric measurements and aortic flow quantification. Myerson et al 2 reported that quantifying MR with CMR showed a strong association with the future need for surgery over the subsequent 5 years, demonstrating the potential value of this approach. Previous studies also suggest only moderate agreement between CMR and echocardiography 3,4 and limited reproducibility for quantitative echocardiographic grading.…”
mentioning
confidence: 99%
“…These CMR parameters might prove useful for identifying suitable patients for early mitral valve repair replacement. 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation